EFFECT OF Fe2+ SUPPLEMENTATION ON GROWTH AND ASTAXANTHIN CONTENT IN HAEMATOCOCCUS PLUVIALIS IN PHOTOBIOREACTOR - ZAHRA (NIM : 11213029), FATHIYAH
Haematococcus pluvialis is a microalgae that can produce astaxanthin (an antioxidant) up to 4% of the dry weight of the cell. The stress condition which is induced by Fe2+ has thought to have role in increasing astaxanthin content in H. pluvialis. Therefore, the objective of this research was to determine the effect of Fe2+ stress driven from iron (II) sulphate heptahidrate on biomass production and astaxanthin content in H. pluvialis. H. pluvialis was cultivated in Rudic medium under light intensity of 40 μmol.m-2s-1 (fluorescent lamp) and aeration at 1.5 vvm (vessel volumes per minute) for 10 days of growth phase to multiply its biomass. After 10 days of cultivation, H. pluvialis was treated with iron (II) sulphate with concentrations of 90, 180, 270, 360, 450 μM, and without Fe2+ addition for 16 days to induce astaxanthin production. The 26 days old H. pluvialis was extracted using methanol:DCM = 1:3 (v/v) by maceration. The extract was then analyzed using HPLC with methanol:water = 95:5 (v/v) as mobile phase at wavelength = 474 nm, respectively. The results showed that the addition of Fe2+ can increase the astaxanthin content in H. pluvialis. The addition of Fe2+ with a concentration of 450 micro M was able to produce the highest astaxanthin content reaching 0.06% of the dry weight of the cell (3 times of control) on day 26th. The highest biomass yield was also obtained in culture with a concentration of 450 μM, which was 26 g biomass/g nitrate. These results suggest that the addition of Fe2+ has the potential to increase astaxanthin content in H. pluvialis without decreasing biomass production.